Isoscalar dipole response of heavy nuclei in low-energy region within kinetic model - V. I. Abrosimov; O. I. Davydovska (Ядерна фізика та енергетика)
The isoscalar dipole response of heavy spherical nuclei in the low-energy region is studied by using a semiclassical model, based on the solution of the linearized Vlasov kinetic equation for finite Fermi systems. In this translation-invariant model, the excitations of the center of mass motion are exactly separated from the internal ones. The isoscalar dipole strength function displays three resonance structures in the energy region up to 15 MeV. Calculations of the velocity fields associated with resonance structures at centroid energies show the vortex (toroidal) nature of two overlying resonances. The main toroidal resonance gives a qualitative description of the low-energy isoscalar dipole resonance, which is observed in heavy spherical nuclei. The origin of the lowest isoscalar dipole resonance structure is apparently related to dipole single-particle excitations. Its centroid energy is close to the minimum energy of the dipole single-particle spectrum, and taking into account the residual interaction leads only to an insignificant shift of the centroid energy towards lower energy. However, the inclusion of residual interaction noticeably enhances the velocity field associated with the lowest resonance, which indicates collective effects in this resonance structure.